The hummingbird in the Nasca Iconography - Valdez, Lidio M. (2025)
Nasca is one of the few cultures of the central Andes that depicted the hummingbird in its iconography. This happened especially during the early phases of Nasca development, when both ceramic vessels and textiles depicted images of the hummingbird. Afterwards, this motif disappears permanently. In this essay we discuss the presence of the hummingbird in the Nasca iconography, its possible symbolic meaning, as well as the possible reasons for its exclusion in later Nasca phases.